Development of silver nanoparticle-based hydrogel composites for antimicrobial activity. Issue 1 (2nd January 2020) - Zakia, Maulida; Koo, Ja Min; Kim, Dowan; Ji, Keunho; Huh, PilHo; Yoon, Jinhwan; Yoo, Seong Il
ABSTRACT: Antimicrobial function of Ag nanoparticles (NPs) has a strong correlation with the released Ag + cations that are produced by oxidation of Ag NPs in a solution state under ambient condition. Therefore, in order to develop anti-infective materials for biomedical applications, one needs to include Ag NPs inside biocompatible materials, which can allow slow release of Ag + cations. Hydrogels of natural polymers could be an ideal choice for the purpose because (a) the physicochemical properties of hydrogels resemble with biological tissue, and (b) the inclusion of Ag NPs inside hydrogels prevents the direct release of Ag NPs, while allowing the release of Ag + cations out of the hydrogels. In this regard, we present a simple strategy for producing Ag NPs-containing hydrogel based on natural alginate polymers. The chemical modification of alginate, blending with Ag NPs, gelation by photo-crosslinking process have been discussed in connection with antimicrobial reaction on model bacterium. GRAPHICAL ABSTRACT: